Pengaruh Minat Belajar Siswa Terhadap Tingkat Kecerdasan Emosional Siswa MTs Negeri 2 Kabupaten Serang - E. Nita Prianti (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
This study aims to determine how much the influence of Student Learning Interests on the Emotional Intelligence of Students in MTs Negeri 2 Serang. This research uses quantitative methods using statistical data through validity, reliability, normality, simple regression linearity and hypothesis testing. The population in this study were 312 MTs students in Serang, while the sample taken in this study was 76 students. The results obtained are that there is a significant influence of learning interest on emotional intelligence of MTs Negeri 2 Serang students. This is evidenced by the acquisition of Fcount = 4,592 with a significance level of 0,000 ≤ 0.05. Furthermore, the variable interest in learning contributed 74.6% to the "Emotional Intelligence of Students in MTs 2 Serang. While the remaining 25.4% is influenced by other factors as a contributor to emotional intelligence. While the acquisition of tcount is 2.143 ≥ 1.995, it means that there is a significant influence between students 'learning interest on students' emotional intelligence in MTs Negeri 2 Serang. In the sense that H0 is rejected and Ha is accepted.